PEMANFAATAN KOTORAN SAPI MENJADI PUPUK ORGANIK - Sumedi P. Nugraha (UII, 2013)
Lack of knowledge of both the theoretical and practical issues of benefits,functionality and how to make organic fertilizer to make the most of the villagersLencoh, Boyolali use chemical fertilizers or inorganic fertilizers as the main material toncrease their agricultural output.Society/ farmers do not quite understand that the longterm use of inorganic fertilizers will erode nutrients and other essential minerals in thesoil causing the soil becomes less fertile and ultimately it will impact on the lack of yieldeven crop failure.The complaints of citizens about the high prices of inorganic fertilizerson the market so that the citizens of the profits generated from agricultural products tobe smaller and less adequate to support the economy of farmers in general. Based onthe above data that the author can be through direct observation and interviews withvillagers Lencoh, the writer took the initiative to conduct counseling and training onhow to make organic fertilizer from cowmanureby using the main ingredient EM-4 plusother materials that exist around citizen. Selection of cowmanureas an alternative toorganic fertilizer is because the average citizen to keep cowas cattle, besides it has beenresident who use manure as fertilizer, but because of lack of knowledge, farmers LencohVillage would make a fatal mistake for direct mix unprocessed manure to agriculturaland.As a consequence it actually makes the disease on plants that they are familiar withthe name